Effect of cadmium on glutathione content of pearl gourami irichogaster leeri tissues - Ibrahim N., Al-Suwiti; Kabbashi, Nassereldeen Ahmed (Enviro Media, 2006)
Data presented on the tissue glutathione content in the liver and kidney of Gourami Trichogaster Leeri exposed for five weeks to sub lethal concentrations of Cadmium. The results indicate that Cadmium caused a marked elevation of glutathione concentrations in both liver and kidney tissue. Glutathione concentration in liver and kidney of Gourami exposed to 10 mg/L Cd were 350% and 400% of control level, respectively. The possibility of detecting environmental pollution by monitoring glutathione concentrations or the activity of glutathione dependent enzymes in fishes is discussed.